Effects of red clover on hot flash and circulating hormone concentrations in menopausal women: a systematic review and meta-analysis - Masumeh Ghazanfarpour; Ramin Sadeghi; Robab Latifnejad Roudsari; Khadijeh Mirzaii Najmabadi; Mojtaba mousavi bazzaz; Somayeh abdolahian; Talat Khadivzadeh (Mashhad University of Medical Sciences, 2015)
Objectives: To critically evaluate the effect of red clover on hot flash, endometrial thickness, and hormones status in postmenopausal and peri- and post-menopausal women. Materials and Methods: MEDLINE (1966 to July 2014), Scopus (1990 to July 2014), and the Cochrane Central Register of Controlled Trials (The Cochrane Library issue 1, 2014) were searched for published randomized controlled Trials (RCTs). Results: Of 183 relevant publication trials, 11 RCTs met the inclusion criteria. The mean hot flashes frequency in red clover was lower than the control groups (MD -1.99; p=0.067). There was larger decrease in FSH (SMD -0.812; CI: -1.93 to 0.312; p=0.157) and SHBG (SMD -0.128; CI-0.425 to 0.170; P=0.4) in red clover group, compared with placebo, which was not however statistically significant. LH (SMD 0.144; CI-0.097 to 0.384, p=0.242), estradiol (SMD 0.240; CI-0.001 to 0.482, p=0.051), testosterone (MD 0.083; CI: -0.560 to 0.726; p=0.901), and endometrial thickness (SDM 0.022; CI: -0.380 to 0.424, p=0.915) showed greater increase in red clover, compared with placebo, although the effect of estradiol was only significant. Conclusion: Red clover had a positive effect of alleviating hot flash in menopausal women. Our data, however, suggested very slight changes in FSH, LH, testosterone, and SHBG and significant effect in estrogen status by red clover consumption. However, the interpretation of results of the current study is limited due to methodological flaws of the included studies, menopause status, and large heterogeneity among them. Further trials are still needed to confirm the current finding.